Penerapan Limit Akses Browsing Internet pada saat Jam Kerja di PT XYZ - Mutaqin Subekti, Zaenal; Mukiman, Kikim; Fikri Adluwal Fadhil, Ahmad; Asyrofi, Muhammad (LPPM STT Terpadu Nurul Fikri, 2021)
One of the engineering companies located in the Cikarang area has a rule that every employee is not allowed to access the internet through a browser during working hours, i.e., from 08.00 AM to 12.00 AM and 1.00 to 5.00 PM, only during break time which is between 12.00 AM until 1.00 PM, employees are allowed to access the internet through a browser. The company can apply this rule by implementing its policies on router firewalls to be followed by all employees thoroughly. This research will analyze and implement the process of configuring the router firewalls for the applied case. The first stage of this research starts from analyzing the software and hardware requirements, analyzing the network topology designs, implement the company's policies on firewall configuration, and the last stage is by doing the testing. From this implementation, we get the results that all users cannot access the internet through a browser except for authorized users. These results are applied based on the company's rules and policies proposed above that employees only able to access the internet through a browser during break time and before and after working hours.